The EFL Students’ Perspective of Their Speaking Competence and Self-Confidence: A Qualitative Study - Sumanto, Ossa Bodhi Tala; Saharani, Annisa Auliya (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The research aims to see students' awareness of their competence based on their self-confidence in speaking English. In this study, the qualitative descriptive approach was employed to collect thorough responses and student views on their speaking ability and confidence level. The researchers introduced respondents to the notion of self-confidence before asking them to complete the questionnaire and conduct an interview. Respondents' confidence appears to be related to their perspective of their speaking ability. Students cannot claim to be at ease every time they speak a foreign language because speaking is such a vital element of communication yet they are motivated to learn and practice English. According to the respondents, while confidence is a fantastic place to start in speaking, it will not take them very far unless they consistently practice enhancing their language competence. The most typical approach is to engage in conversation whenever feasible.